THE RELATIONSHIP BETWEEN HEALTH EDUCATION AND PREGNANT WOMEN'S KNOWLEDGE AND ATTITUDES REGARDING POSTPARTUM FAMILY PLANNING AT THE ANNASR CISAUK MAIN CLINIC, TANGERANG REGENCY IN 2023 - Dewi, Prima Thiarani; Wintarsih, Wintarsih (HEARTY, 2025)
Background: the use of birth control during postpartum before 6 weeks or 42 days will be able to prevent unwanted pregnancy. Knowledge and attitudes are factors that influence the use of birth control after childbirth. One effort to increase mothers' knowledge and attitudes about postpartum family planning is through health education provided both through classes for pregnant women and during third-trimester counseling visits. Objective: to determine the relationship between health education and the knowledge and attitudes of pregnant women regarding postpartum family planning at the Annasr Cisauk Main Clinic, Tangerang Regency in 2023. Research method: quantitative analysis with cross-sectional design. The research sample was 52 third-trimester pregnant women using an accidental sampling technique. The research instrument used a questionnaire. The data is primary data analyzed using the chi-square test. Research results: univariate analysis showed that the majority of pregnant women received health education about postpartum family planning, 67.3%, with good knowledge 63.5% and positive attitudes 69.2%. The results of the bivariate analysis showed a relationship between health education and pregnant women's knowledge (p-value = 0.000) and pregnant women's attitudes (p-value = 0.006) regarding postpartum family planning. Conclusions and Suggestions: there is a relationship between health education and pregnant women's knowledge and attitudes about postpartum family planning. Midwives are expected to provide health education to all pregnant women in the third trimester regarding the use of birth control contraceptives after giving birth before 42 days so that after giving birth the mother will consciously want to use them as an effort to shorten pregnancy.